FEMALE STEREOTYPES PRESENTED IN“CANTIQ” TABLOID - FACHRANI, JOAN ISMA AYU ASTRI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Culturally, people in different parts of the world arrange themselves in apatriarchal society. Patriarchal culture is contributing greatly to marginalizewomen with gender roles which seem to be determined entirely and naturalized bypatriarchal society, this phenomena is called as female stereotype. Language(discourse) also takes a part to create the constructions of gender, ideology andstereotype, eventually adapted by women tabloids as a mass media having powerto spread their "messages". Crit ical Discourse Analysis (CDA) sees discourse as a"social pract ice" which can give social impact to the societ y. This study isconducted to figure out the meaning constructions conveyed in "Cant iq" tabloidheadlines and to find out female stereotype presented by "Cant iq" tabloid.This study uses qualitative approach, and there are two types of the studyused; content or document analysis and case study. The writer uses criterion casesampling to find out participants. The participants of this study are the readers of"Cantiq" tabloid consisting of 2 women from young adulthood and 2 women frommiddle adult hood. The data are taken from "Cant iq" tabloid headlines duringJanuary 2013 to February 2013, and the interview results from the participants.This study finds that there are two meaning construction emerged from theheadlines. Those are "women should not be fat" and "physical beauty is full ofrisk". This study also found that there are two female stereotype interpreted by thereaders of "Cant iq" tabloid; "women should be slim and apply make up" and"women should be attractive to men". Those utterances reflect patriarchal, sincewomen are considered as a second sex and their bodies are treated as an object.The participants believe it can give social impacts to the society and determinewhat is the construction of female beauty. The readers and society will finallyaccept the idea saying that beauty is equal to having slim body figure, applyingmake up, and having cosmetics procedures to look attractive.The writer suggests that the next writer will also cover up socioculturalpractice by using case study because it is important to use participants point ofview as a part of the society since CDA is related with language as a form ofsocial practice. Keywords: female stereotype, patriarchal society, Critical Discourse Analysis(CDA)